2020
DOI: 10.1016/j.ekir.2020.08.017
|View full text |Cite
|
Sign up to set email alerts
|

Survey of US Living Kidney Donation and Transplantation Practices in the COVID-19 Era

Abstract: Introduction: The scope of the impact of the COVID-19 pandemic on living donor kidney transplantation (LDKT) practices is not well defined. Methods: We surveyed US transplant programs to assess practices, strategies, and barriers to living LDKT during the COVID-19 pandemic. After institutional review board approval, the survey was distributed from 9 May 2020 to 30 May 2020 by e-mail and postings to professional society list-servs. Responses were stratified based on state COVID-19 cumulative incidence levels. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
80
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 59 publications
(83 citation statements)
references
References 18 publications
3
80
0
Order By: Relevance
“…A survey of U.S. programs in May 2020 identified multiple barriers to living donation and LDKT surgery during the early phase of the pandemic, including program concerns for donor (85%) and recipient (75%) safety, patient concerns (56%), elective case restrictions (47%), and hospital administrative restrictions (48%). 7 Programs with higher local COVID-19 cumulative incidence reported more barriers related to staff and resource diversion.…”
Section: Suspension Of Practice: When Is It Necessary?mentioning
confidence: 97%
See 3 more Smart Citations
“…A survey of U.S. programs in May 2020 identified multiple barriers to living donation and LDKT surgery during the early phase of the pandemic, including program concerns for donor (85%) and recipient (75%) safety, patient concerns (56%), elective case restrictions (47%), and hospital administrative restrictions (48%). 7 Programs with higher local COVID-19 cumulative incidence reported more barriers related to staff and resource diversion.…”
Section: Suspension Of Practice: When Is It Necessary?mentioning
confidence: 97%
“…5,6 The rationale for the dramatic disruption of practices early on included categorizing LDKT as 'elective' (i.e., distinct from some 'essential' DDKT) and possible to safely delay, especially in locations with strained resources including the availability of ventilators (Figure 1). 7 Further, LDKT has additional complexity related to safety concerns both for the recipient, as early reports suggested that transplant recipients face substantially increased mortality risks following severe acute respiratory syndrome coronavirus 2 (SARS CoV 2) infection, 8,9 and also for the living donor. A by-proxy effort to synthesize consensus based on 19 professional society bulletins published in March J o u r n a l P r e -p r o o f 2020 offered strong agreement (14/19) for reduction to a minimum, if not complete postponement, of 'elective' transplantation, in particular LDKT, during the pandemic.…”
Section: Suspension Of Practice: When Is It Necessary?mentioning
confidence: 99%
See 2 more Smart Citations
“…1 Telemedicine has allowed transplant centers to sustain pretransplant evaluations of kidney failure patients and potential live kidney donors and post-transplant continuity of care for both the recipient and donor. 13 Moreover, telemedicine provides prompt and safe approach to transplant patients with COVID-19. We have developed a practical workflow process using telemedicine to manage kidney transplant patients with COVID-19 while avoiding emergency room or clinic visit, which is especially important for such immunosuppressed patients who may have prolonged viral shedding.…”
Section: Telemedicine Practice During Covid-19mentioning
confidence: 99%